Longitudinal relationships of psychotic-like experiences with suicidal ideation and self-harm in adolescents: original contribution - Zhou, Rui; Foo, Jerome Clifford; Nishida, Asuka; Ogawa, Sayoko; Togo, Fumiharu; Sasaki, Tsukasa (European child & adolescent psychiatry, 2023)
Research in adolescents suggests associations between psychotic-like experiences (PLEs) and self-injurious thoughts and behaviors (SITBs), but insights into their temporal relationship, which may inform prediction, have been limited. Psychological distress (PD; symptoms of depression and anxiety) has been related to both PLEs and SITBs, and may modulate this relationship. Given that PLEs have been linked to the development of several mental disorders, and the relationships between SITBs and suicide, it is important to better understand their relationship. The present study sought to investigate these factors using a longitudinal school-based design. Adolescents (n = 1685, ages 12-18) completed annual self-report assessments (6 time points) on PLEs, SITBs (suicidal ideation (SI) and self-harm (SH)), as well as PD. The longitudinal associations between PLEs and SITBs were analyzed, employing two cross-lagged panel models (CLPMs), with and without adjustment for PD. Unadjusted CLPMs revealed significant bidirectional temporal associations between PLEs and SITBs (both SI and SH), suggesting that PLEs both predicted and were predicted by SITBs. When adjusting for PD, the effect of SI on PLEs remained significant, but not PLEs on SI; bidirectional associations between PLEs and SH also remained significant. A bidirectional longitudinal relationship where both PLEs and SITBs can precede (and perhaps predict) each other was suggested in adolescents. PD may play a particular role in situations where PLEs are followed by SI. Heightened awareness about relationships between these phenotypes may be an important step toward facilitating timely interventions for both mental disorders and suicide.
Gesehen am 18.03.2024